Implementasi Perda Nomor 12 Tahun 2019 Dalam Upaya Penanggulangan Bencana di Kelurahan Tanjungmekar Kecamatan Karawang Barat Kabupaten Karawang - Sri Supriyani; Hartono Hartono; Anita Maulina (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the implementation of Regional Regulation Number 12 of 2019 on Disaster Management in Tanjungmekar Sub-district, West Karawang District, Karawang Regency. The research aims to analyze the policy implementation, identify obstacles, and evaluate strategies to address them. A qualitative approach with field research design was employed. Data were collected through interviews, observations, and documentation involving 6 key informants from government institutions, related agencies, and the community. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing/verification. The analysis also applied George C. Edwards III’s theory, emphasizing communication, resources, disposition, and bureaucratic structure as key variables of policy implementation. The findings indicate that the regulation has been moderately well-implemented, supported by clear bureaucracy and inter-agency communication. However, challenges persist, including limited human resources, insufficient budget, weak coordination, low community participation, absence of technical guidelines, and lack of regular evaluation.